Molecular nanomagnets - Gatteschi, D.; Sessoli, Roberta; Villain, Jacques (Mesoscopic physics and nanotechnology ;, 2006)
Molecular nanomagnetism is a research area of interest to chemists and physicists who want to discover the beauty of the molecular world and its potentialities to give new classes of magnetic materials. This book is ideal for researchers, PhD students and post docs in magnetism, solid state physics, and molecular chemistry.